Dosis de nitrógeno sobre las carácterísticas agronómicas y nutricionales en forraje de Zea mays L. (Maíz amarillo Duro), var. Marginal 28 tropical Yurimaguas – Perú - Vasquez Cisneros, Susan Gabriela (2018)
The research was carried out in the agroecological site of the city of Yurimaguas, 8.5 km from the Yurimaguas - Tarapoto highway, which has the title "Nitrogen dose on the agronomic and nutritional characteristics of Zea mays L. forage (hard yellow corn). , var. Marginal 28 tropical - Yurimaguas - Peru". The applied inorganic fertilizer was urea (46% nitrogen). The cutting time was 60 days after sowing with botanical seeds, in plots of 4.5 m2 of area and 161.5 m2 of total area, established in an Ultisol soil. The statistical design used was a Design of Block Completely Random (DBCA), with four treatments and four repetitions, using the statistical package of Inforstat, the treatments under study were: T0 (0 kilos of nitrogen / ha), T1 (80 kilos of nitrogen / ha), T2 (160 kilos of nitrogen / ha) and T3 (240 kilos of nitrogen / ha). For these agronomic characteristics the one that occupied the first place in order of merit was T3 (180 kg of Nitrogen / ha), in height with 1.46 m, green matter of 3.76 kg / m2, dry matter of 0.79 kg / m2, having a positive response to the increasing application of nitrogen, in yield in green matter and dry treatment T3 (240 kg N / hectare), 37,600 kilos / ha / cut and 7,900 kilos of dry matter per hectare cut was achieved. In the nutritional value, the percentage of protein (7.7%) and fat (2.23%) the T3 treatment (240 Kg N / ha), occupies the first places, on the other hand the treatment T0 (0 Kg N / ha) in the indicator’s percentage of fiber (30.35%) and ash (1.46%)